2022
DOI: 10.3390/cancers14020316
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib Treatment Alone or with Bevacizumab in a Real-World Cohort of Non-Small Cell Lung Cancer Patients with Epidermal Growth Factor Receptor Mutation

Abstract: Background: Treatment outcome between afatinib alone or with bevacizumab in non-small cell lung cancer (NSCLC) patient with epidermal growth factor receptor (EGFR) mutation remains insufficiently reported. Methods: A total of 405 advanced NSCLC patients with sensitizing-EGFR mutation receiving first-line single-agent afatinib or with bevacizumab were grouped and propensity score-matched. Progression-free survival (PFS), overall survival (OS) and secondary T790M mutation were analyzed. Results: In the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous prospective clinical trials showed that erlotinib combined with bevacizumab significantly prolonged PFS compared to erlotinib alone but had no significant effects on OS 23–25 . Our recent real‐world cohort studies showed that patients receiving only afatinib treatment had a median PFS (16.1 months vs. 15.0 months; p = 0.500) and median OS (32.1 months vs. 42.0 months; p = 0.700) similar to those of patients receiving afatinib plus bevacizumab 26 . Afatinib combined with bevacizumab was equally as effective as erlotinib combined with bevacizumab in terms of the objective response rate, disease control rate, median PFS, and median OS 27 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous prospective clinical trials showed that erlotinib combined with bevacizumab significantly prolonged PFS compared to erlotinib alone but had no significant effects on OS 23–25 . Our recent real‐world cohort studies showed that patients receiving only afatinib treatment had a median PFS (16.1 months vs. 15.0 months; p = 0.500) and median OS (32.1 months vs. 42.0 months; p = 0.700) similar to those of patients receiving afatinib plus bevacizumab 26 . Afatinib combined with bevacizumab was equally as effective as erlotinib combined with bevacizumab in terms of the objective response rate, disease control rate, median PFS, and median OS 27 .…”
Section: Discussionmentioning
confidence: 78%
“… 23 , 24 , 25 Our recent real‐world cohort studies showed that patients receiving only afatinib treatment had a median PFS (16.1 months vs. 15.0 months; p = 0.500) and median OS (32.1 months vs. 42.0 months; p = 0.700) similar to those of patients receiving afatinib plus bevacizumab. 26 Afatinib combined with bevacizumab was equally as effective as erlotinib combined with bevacizumab in terms of the objective response rate, disease control rate, median PFS, and median OS. 27 In the present study, median PFS and median OS did not differ significantly between patients receiving the afatinib and bevacizumab combination and those receiving afatinib only (13.8 vs. 14.5 months [ p = 0.782] and 37.5 vs. 26.3 months [ p = 0.052], respectively).…”
Section: Discussionmentioning
confidence: 91%
“…A multicenter observational study reported that the first-line afatinib plus bevacizumab demonstrated an ORR of 87.7%, a median PFS of 23.9 months, and a median OS of 45.9 months. Further prospective studies are warranted to confirm the clinical efficacy [37,38]. In addition, immunotherapy plus chemotherapy tended to be more effective than immunotherapy alone in previously TKI-treated NSCLC harboring EGFR mutations [39].…”
Section: Egfrmentioning
confidence: 95%
“…In a retrospective study, alternative treatment with Chinese herbal medicine (CHM) during first-line EGFR-TKI showed a tolerable toxicity profile and a tendency toward better progression-free sur-vival (PFS)and overall survival (OS) than those who did not receive CHM [35]. Multiple studies have reported that not only erlotinib plus bevacizumab, but also afatinib combined with bevacizumab, demonstrated favorable efficacy for the first-line treatment of advanced pulmonary adenocarcinoma harboring EGFR mutations [36][37][38]. A multicenter observational study reported that the first-line afatinib plus bevacizumab demonstrated an ORR of 87.7%, a median PFS of 23.9 months, and a median OS of 45.9 months.…”
Section: Egfrmentioning
confidence: 99%
“…ARTEMIS-CTONG1509, a multicenter phase-III study, found that bevacizumab (an anti-VEGF antibody) plus erlotinib significantly improved PFS in patients with EGFR-mutated NSCLC, including those with brain metastases at the baseline ( 119 ). Kuo et al found that a bevacizumab combination treatment showed moderate efficacy in afatinib-treated NSCLC patients with the EGFR-sensitizing mutation ( 120 ). However, a treatment of osimertinib plus bevacizumab failed to show any efficacy in improving the PFS of EGFR-mutated NSCLC patients, with similar findings reported in the studies of Soo et al and Kenmotsu et al ( 121 , 122 ).…”
Section: Egfr-tkis Combined With Immunotherapymentioning
confidence: 99%